2021
DOI: 10.1186/s12905-021-01189-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in access to healthcare for women with disabilities: a systematic review in qualitative studies

Abstract: Background Studies show that different socio-economic and structural factors can limit access to healthcare for women with disabilities. The aim of the current study was to review barriers in access to healthcare services for women with disabilities (WWD) internationally. Methods We conducted a systematic review of relevant qualitative articles in PubMed, Web of Science and Scopus databases from January 2009 to December 2017. The search strategy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 76 publications
5
58
1
6
Order By: Relevance
“…Diagnosis of ID had an equivocal effect on both contraception counseling and use of contraception. This runs counter to current literature on sexual health in women with ID, where the presence of ID decreases the likelihood of reproductive planning [ 17 ]. Metabolic physicians may be uniquely suited to have such conversations with patients with ID because of strong rapport with patients and their families due to longstanding relationships.…”
Section: Discussioncontrasting
confidence: 84%
“…Diagnosis of ID had an equivocal effect on both contraception counseling and use of contraception. This runs counter to current literature on sexual health in women with ID, where the presence of ID decreases the likelihood of reproductive planning [ 17 ]. Metabolic physicians may be uniquely suited to have such conversations with patients with ID because of strong rapport with patients and their families due to longstanding relationships.…”
Section: Discussioncontrasting
confidence: 84%
“…Evidence suggests that, in many settings with limited resources (such as Indonesia), people with a disability, including children, still experience difficulties in accessing healthcare, rehabilitation, and social support services. For example, the poor financial situation of parents is one of the main barriers to access to services [ 4 , 5 , 6 , 7 , 8 , 9 ]. Studies in a number of low- and middle-income countries (LMICs) have identified financial barriers, such as the inability of parents to afford the costs for healthcare or treatment services [ 10 , 11 , 12 , 13 ], health insurance [ 14 ], and/or social protection [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the poor financial situation of parents is one of the main barriers to access to services [ 4 , 5 , 6 , 7 , 8 , 9 ]. Studies in a number of low- and middle-income countries (LMICs) have identified financial barriers, such as the inability of parents to afford the costs for healthcare or treatment services [ 10 , 11 , 12 , 13 ], health insurance [ 14 ], and/or social protection [ 9 , 15 ]. Social factors, such as stigma and discrimination from community members and healthcare providers towards people with a disability (leading to embarrassment by parents to be “seen” with their child in public), have also been reported as barriers for access to healthcare and rehabilitation services [ 7 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results are congruent with a recent systematic review that reported a lack of accessible equipment in healthcare sites, inaccessible buildings, and transportation costs were barriers to healthcare access for women with J o u r n a l P r e -p r o o f disabilities. 45 These are not simple inconveniences -the basic standard of care that is expected for patients in Canadian healthcare contexts cannot be met for these women when they must have a physical examination performed in their wheelchair because they are unable to get on an examination table in a clinic. Such experiences are consistent with the findings of Stillman et al 46 in the United States, where wheelchair users were found to be less likely to receive adequate physical examinations and other preventative care.…”
Section: Discussionmentioning
confidence: 99%